Experimental Analysis of Conical Basin Models with Vortex Turbines for Small-Scale Renewable Energy Generation - Kurniawan, Iwan; Romy, Romy; Hamzah, Amir; Farhan, A (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This study investigates the performance of Gravitational Water Vortex Turbines (GWVT) using different conical basin configurations, focusing on the impact of vane designs on turbine efficiency. Four basin models were tested: model A (no vanes), Model B (180-degree vanes), Model C (90-degree vanes), and Model D (45-degree vanes). The basin was constructed from resin mixed with fiber, with the addition of vanes designed in various configurations to enhance vortex formation and energy extraction. Experimental testing was conducted under varying load conditions, with efficiency determined by the ratio of the potential energy of the water to the mechanical energy generated by the turbine. The results showed a significant improvement in efficiency with the introduction of vanes. Model B, featuring 180-degree vanes, demonstrates the highest efficiency, achieving an increase of up to 17.08% compared to the base model (Model A). Model C, with 90-degree vanes, and Model D, with 45-degree vanes, show efficiency increases of 14.56% and 12.08%, respectively. These results imply that the design and arrangement of vanes are essential in enhancing vortex formation and turbine performance.